Question : An example of an equality relation of two expressions in $x$. Which is not an identity, is:

Option 1: $(x+3)^{2}=x^{2}+6x+9$

Option 2: $(x+2y)^{3}=x^{3}+8y^{3}+6xy(x+2y)$

Option 3: $(x+2)^{2}=x^{2}+2x+4$

Option 4: $(x+3)(x–3)=x^{2}–9$


Team Careers360 1st Jan, 2024
Answer (1)
Team Careers360 7th Jan, 2024

Correct Answer: $(x+2)^{2}=x^{2}+2x+4$


Solution : Given: $(x+3)^{2}=x^{2}+6x+9$
⇒ $(x^{2}+9+6x)=x^{2}+6x+9$
Similarly, $(x+2y)^{3}=x^{3}+8y^{3}+6xy(x+2y)$
⇒ $x^{3}+8y^{3}+6xy(x+2y)=x^{3}+8y^{3}+6xy(x+2y)$
Similarly, $(x+3)(x–3)=x^{2}-9$
Similarly, $(x+2)^{2}=x^{2}+2x+4$
⇒ $(x^{2}+4+4x)=x^{2}+2x+4$
We can see this is not an identity.
Hence, the correct answer is '$(x+2)^{2}=x^{2}+2x+4$'.

Know More About

Related Questions

TOEFL ® Registrations 2024
Apply
Accepted by more than 11,000 universities in over 150 countries worldwide
Manipal Online M.Com Admissions
Apply
Apply for Online M.Com from Manipal University
GRE ® Registrations 2024
Apply
Apply for GRE® Test now & save 10% with ApplyShop Gift Card | World's most used Admission Test for Graduate & Professional Schools
View All Application Forms

Download the Careers360 App on your Android phone

Regular exam updates, QnA, Predictors, College Applications & E-books now on your Mobile

150M+ Students
30,000+ Colleges
500+ Exams
1500+ E-books